Applying AHP for Assessing Zenbo Division Production Employee Performance: Penerapan Metode AHP untuk Menilai Kinerja Karyawan Produksi Divisi Zenbo - Prasetyo, Doni; Marodiyah, Inggit (Universitas Muhammadiyah Sidoarjo, 2024)
This research proposes an employee assessment system utilizing the Analytical Hierarchy Process (AHP) method to evaluate productivity levels. The absence of such a system poses challenges in gauging employee performance and its impact on company productivity. Through AHP, this study aims to provide decision support for performance evaluation, thereby maintaining high productivity levels. Results indicate significant shifts in employee rankings, highlighting the effectiveness of the proposed methodology in identifying and enhancing productivity. This research contributes to the discourse on employee performance assessment, offering practical implications for decision-makers aiming to optimize workforce productivity. Highlights : Enhanced decision-making: The utilization of AHP provides a structured approach for evaluating employee performance, facilitating informed decision-making processes. Improved productivity rankings: Implementation of the assessment system results in notable shifts in employee rankings, indicating its effectiveness in identifying high-performing individuals. Practical implications: Findings offer valuable insights for organizations seeking to optimize workforce productivity through systematic performance evaluation methodologies. Keywords: Employee productivity, Assessment system, Analytical Hierarchy Process (AHP), Decision support, Workforce optimization